اﺿطراب اﻟﺳﻠوك اﻟﺗواﺻﻠﻲ وﻋﻼﻗﺗﮫ ﺑﺎﻹﺳﻧﺎد اﻻﺟﺗﻣﺎﻋﻲ ﻋﻧد اﻟﺗﻼﻣذة اﻷﯾﺗﺎم وﻏﯾرھم )ﺑﺣث ﻣﺳﺗل ﻣن رﺳﺎﻟﺔ ﻣﺎﺟﺳﺗﯾر( (Journal of the College of Education for Women, 2019)
This study aims at: Finding out the degree of conduct disorder of the orphan and non-orphans pupils in the sample of the study,and finding out the degree of social support of the orphan and non-orphans pupils in the sample of the study,and finding out, the degree of relationship between conduct disorder and social support of the members in the sample of the study,and finding out significant differences among the members in the sample of the study that depends on a scale of conduct disorder and social support according to the following variables: .The type of sample members (orphans, non-orphans). .Gender(males,females), (orphans,non-orphans).study sample consisted of (300) males and females of orphan and non-orphan pupils in fifth and sixth grade of primary school, half male and half female.The researcher used a conduct disorder scale prepared by the researcher and social support scale which was also prepared by the researcher.The results of the study showed that the degree reduction of conduct disorder inside the school many orphans and non- orphans, and the results of the study showed that the degree height of social support of orphan and nonorphanpupils, the results of the study also showed that the inverse relation between conduct disorder and social support in the sample of the study, the results of the study showed that the differences have been indicatined in conduct disorder in variables if gender and causel (orphans, non-orphan) or the benefit of orphan males and females,and the differences have been indicatined in social support of variables gender and causel (orphans, non-orphans) for the benefit of non- orphan males and females of (0.05) level.